Effect of shaking speed on immobilization of cephalosporin C acylase: Correlation between protein distribution and properties of the immobilized enzymes. (5th September 2020) - Liu, Jingran; Tong, Shuangming; Sun, Hongxu; Chang, Yanhong; Luo, Hui; Yu, Huimin; Shen, Zhongyao
Abstract: During enzyme immobilization, enzyme activity and protein distribution are affected by various factors such as enzyme load, temperature, and pH. In general, two types of protein distribution patterns (heterogeneous or homogeneous) are observed inside a porous carrier, owing to differences in preparation parameters. During the immobilization of a fusion protein (CCApH) of cephalosporin C acylase (CCA) and pHluorin (a pH‐sensitive mutant of green fluorescent protein), different shaking speeds induced obvious differences in protein distribution on an epoxy carrier, LX‐1000EPC. Enzyme immobilization with a homogeneous distribution pattern was observed at a low shaking speed (120 rpm) with an operational stability of 10 batches at 37°C. The operational stability of an immobilisate with heterogeneous protein distribution prepared at a high shaking speed (200 rpm) was six batches. Given the pH‐sensitive characteristics of pHluorin in the fusion protein, the intraparticle pH of CCApH immobilisates during catalysis was monitored using confocal laser scanning microscopy. The microenvironmental pH of the immobilisate with heterogeneous protein distribution sharply decreased by about 2 units; this decrease in the pH may be detrimental to the life‐span of immobilized CCA. Thus, this work demonstrates the good operational stability of pH‐sensitive proton‐forming immobilized enzymes with homogeneous protein distribution.